2007
DOI: 10.1111/j.1365-2567.2007.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in non‐obese diabetic mice is not associated with quantitative changes in CD4+ CD25+ Foxp3+ regulatory T cells

Abstract: Summary The role of regulatory T cells (Tregs) in maintaining self tolerance has been intensively researched and there is a growing consensus that a decline in Treg function is an important step towards the development of autoimmune diseases, including diabetes. Although we show here that CD25+ cells delay diabetes onset in non‐obese diabetic (NOD) mice, we found, in contrast to previous reports, neither an age‐related decline nor a decline following onset of diabetes in the frequency of CD4+ CD25+ Foxp3+ regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
90
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 46 publications
13
90
0
Order By: Relevance
“…Since anti-CD25 antibodies do not always deplete CD25 + T cells [27], but rather inhibit their function [37], the cytokine environment might be less favourable for expansion of the CD25 − FOXP3 + T cells [39]. Reactive changes in CD25, CD62L and FOXP3 as phenotypic markers of putative Treg have been previously observed with immunomodulatory agents such as Cy, anti-IL-2, anti-CD25 and anti-CD3, and have been generally associated with positive outcome of immunomodulation in NOD mice [4,5,16,28]. A similar reactive increase in FOXP3 expression has recently been associated with beneficial effects of Treg activation achieved by several immunomodulatory modalities, including IL-2/IL-2 antibody complexes, anti-thymocyte globulin, complete Freund's adjuvant, vasoactive intestinal peptide and rapamycin [18,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since anti-CD25 antibodies do not always deplete CD25 + T cells [27], but rather inhibit their function [37], the cytokine environment might be less favourable for expansion of the CD25 − FOXP3 + T cells [39]. Reactive changes in CD25, CD62L and FOXP3 as phenotypic markers of putative Treg have been previously observed with immunomodulatory agents such as Cy, anti-IL-2, anti-CD25 and anti-CD3, and have been generally associated with positive outcome of immunomodulation in NOD mice [4,5,16,28]. A similar reactive increase in FOXP3 expression has recently been associated with beneficial effects of Treg activation achieved by several immunomodulatory modalities, including IL-2/IL-2 antibody complexes, anti-thymocyte globulin, complete Freund's adjuvant, vasoactive intestinal peptide and rapamycin [18,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 98%
“…Impact of cyclophosphamide and IL2-cas on diabetes in NOD mice In view of the evidence that IL2-cas induces apoptosis in CD25 + T cells and decreases effector activity, the fusion protein was evaluated in NOD mice in vivo. On the one hand, an agent that mediates targeted killing of CD25 + T cells is expected to precipitate early onset of diabetes similar to cyclophosphamide [4][5][6] and anti-CD25 antibodies [27,28]. On the other hand, decreased activity of reactive cells suggests that the fusion protein might ameliorate the course of insulitis as observed with diphtheria toxin in NOD mice [20] and IL2-cas in inflammatory colitis [22,23,25].…”
Section: Il2-cas Suppresses Effector Cellsmentioning
confidence: 99%
“…As they are FoxP3 + , these regulatory T cells are most consistent with 'natural' regulatory T cells, which characteristically exert their suppressive effects in an IL-10-independent but contact-dependent manner. While development of diabetes in NOD mice is not associated with changes in the numbers of natural regulatory T cells, 30,31 there is mounting evidence that development of type 1 diabetes is associated with a qualitative defect in regulatory T-cell function. The suppressive capability of natural regulatory T cells of NOD mice decreases with age 32 and T-regulatory cells expanded from 4-week-old NOD mice are more protective against diabetes than those expanded from older NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…How, when, and why peripheral immunological tolerance is progressively lost and the disease is initiated, is a matter of investigation. One of was challenged and it was suggested that the decline may reflect contamination of the CD4 + CD25 + "Treg" cells with Foxp3 − cells that lack regulatory capacity [7]. However, control of diabetogenic T-cell activity may still be defective since conventional T (Tconv) cells from older NOD mice were found to be relatively resistant to suppression by Treg cells [5,6,8].…”
Section: Introductionmentioning
confidence: 99%